Effect treatment the soil by some pesticide jungles on antagonistic ability for fungus Trichoderma harzianum against rice diseases fungi - yas Lahmood, Walaa (Al-Qadisiyah Journal of Pure Science, 2018)
This study included testing the antagonistic ability of fungus Trichoderma harzianum that isolated from soil of rice fields that treated and not treated with three herbicides that are Azimsulfuron , Oxadiazon and Bispyrabic sodium, then studied the four treatments of filterates antagonistic fungus that isolated from untreated and treared soil herbisides on the rice pathogenic fungi such as Curvularia lunata , Penicillium notatium , Rhizoctonia solani and Fusarium solani ,testing the effects of antagonistic filterare on radial growth and dry weight on pathogenic fungi . the results appeared the more treatment effective on radial growth of pathogenic fungi , it’s the treatment of antagonistic fungus filterate that isolated from soil field treated with herbicide Azimsulfuron the rates of radial growth about (10.6, 9.6, 8.3,10.3) for fungi for fungi (C.lunata ,P.notatium ,F. solani ,R.solani) respectively. Also the results appeared that the most treatments reduced the dry weight of pathogen fungi was the treatment of antagonistic fungus filterate that isolated from soil fields treated with herbicide Azimsulfuron. Also study testing the ability of antagonistic fungus on production some lysozyme enzyme such as chitinase , protease, amylase in special growth medium , the more treatment for antagonistic fungi that production the lysozyme enzyme was antagonistic fungus filterate that isolated from soil fields that treated with herbicides Azimsulfuron.